2019
DOI: 10.1002/etc.4305
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria reduce motility of quagga mussel (Dreissena rostriformis bugensis) sperm

Abstract: The temporal expansion of harmful algal blooms, primarily associated with cyanobacteria, may impact aquatic organisms at vulnerable life-history stages. Broadcast spawning species release gametes into the water column for external fertilization, directly exposing sperm to potential aquatic stressors. To determine if cyanobacteria can disrupt reproduction in freshwater broadcast spawners, we evaluated sublethal effects of cyanobacteria exposure on quagga mussel (Dreissena rostriformis bugensis) sperm. In labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Interestingly, we found that iron deficiency produced marked disturbances to the intestinal microbiota, and these disturbances dysregulated spermatogenesis. The extracts and exudates of Cyanobacteria have oestrogenic activity (Sychrová et al, 2012) and reduced sperm motility of the quagga mussel (Dreissena rostriformis bugensis) (Boegehold et al, 2019). The evidence suggests that Cyanobacteria is detrimental to spermatogenesis; however, we surprisingly found that the presence of Cyanobacteria is vital for normal spermatogenesis, as it was barely detectable in the gut of iron-deficient mice.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Interestingly, we found that iron deficiency produced marked disturbances to the intestinal microbiota, and these disturbances dysregulated spermatogenesis. The extracts and exudates of Cyanobacteria have oestrogenic activity (Sychrová et al, 2012) and reduced sperm motility of the quagga mussel (Dreissena rostriformis bugensis) (Boegehold et al, 2019). The evidence suggests that Cyanobacteria is detrimental to spermatogenesis; however, we surprisingly found that the presence of Cyanobacteria is vital for normal spermatogenesis, as it was barely detectable in the gut of iron-deficient mice.…”
Section: Discussionmentioning
confidence: 69%
“…Mechanistically, defects in these activities appear to be a consequence of transcriptional mis-regulation of genes essential for testicular development. Moreover, iron deficiency impairs spermatogenesis indirectly by affecting hormone synthesis and testicular microbial homeostasis, evidenced by the DEGs, differentially expressed metabolites and functional prediction of differentially expressed microbiota (Zhang et al, 2022;Babakhanzadeh et al, 2020). Although we have deeply analysed the harm exerted by iron deficiency on spermatogenesis from different angles and have identified the regulation of ceRNA networks, we have not identified the key genes that are affected by iron deficiency and lead to spermatogenesis disorders.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some functional traits of cyanobacteria, including cell size, life form (e.g. single celled, colonial, or filamentous), nutritional deficiency, and toxin production, can prevent them from being grazed by mussels ( White and Sarnelle, 2014 ; Boegehold et al, 2019 ). For example, Corbicula fluminea selectively filtered particles in the range of 0.2–2 µm ( Rong et al., 2021 ), Dreissena Polymorpha preferred food particles from 5 to 40 μm ( Sprung & Rose, 1988 ), and Venerupis corrugatus filtered out particles of 5 to 13 μm ( Stenton-Dozey and Brown, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Production and maintenance of early life stages in the laboratory can be laborious, and success depends on culture methods (e.g., pH and alkalinity of culture water; Fisher et al, 1994) and the ability to maintain adults in spawning condition (Stoeckel et al, 2004). For laboratory spawning and culture methods, see Fisher et al (1994); Nichols (1992); Ram & Nichols (1992); Ram et al (1996); Wright, Setzler‐Hamilton, Magee, Kennedy, & McIninch (1996); Wright, Setzler‐Hamilton, Magee, & Harvey (1996), Stoeckel et al (2004), and Boegehold, Alame, et al (2018); and Boegehold, Johnson, et al (2018).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%